Distributed event-triggered control for consensus of multi-agent systems. Issue 9 (September 2015) - Zhang, Hao; Yang, Ruohan; Yan, Huaicheng; Chen, Qijun
Abstract This paper investigates the consensus problem of a class of multi-agent systems with single-integrator. Two novel distributed event-triggered control schemes are developed, which can reduce the frequency of the controller updates and the communication load. It is shown that under the proposed control protocols, consensus can be reached if the underlying communication graph of the multi-agent systems is connected and both the computation cost and communication cost are saved. Finally, the effectiveness of the theoretical results is illustrated by a simulation example.